Determination of the antenna heterogeneity of Photosystem II by direct simultaneous fitting of several fluorescence rise curves measured with DCMU at different light intensities - Lazár, D; Tomek, P; Ilík, P; Naus, J (Photosynthesis research, 2001)
Several methods for determination of the antenna heterogeneity of Photosystem II from fluorescence rise curves measured with DCMU have been developed so far. Using these methods, two, three or four types of Photosystem II with respect to the antenna heterogeneity were determined. However, the accuracy of some of these methods is under debate. Here, we present a new method for the determination of the antenna heterogeneity of Photosystem II. The method is based on direct simultaneous fitting of several fluorescence rise curves measured with DCMU at different intensities of light excitation. As several curves measured under different light conditions are fitted simultaneously by the same model, reliability and accuracy in determination of model parameters increase. Our method was applied to two plant materials with different structure of the thylakoid membrane: wheat leaves and cells of green alga Chlamydomonas reinhardtii.